Mixing of isoscalar and isovector characteristics in the low-energy dipole mode - Inakura, Tsunenori; Ebata, Shuichiro (Frontiers in Physics, 2024)
We investigated isospin splitting in low-energy dipole (LED) states of spherical nuclei such as 40Ca, 90Zr, 132Sn, 208Pb, and several N=50 isotones using self-consistent Hartree–Fock plus random phase approximation calculations. Our analysis of isovector dipole (IVD) and isoscalar dipole (ISD) strengths, along with transition densities, reveals a clear energy-dependent relationship between IS and IV modes in 40Ca and 90Zr. For 208Pb and 132Sn, LED states show mixed IS + IV characteristics due to different neutron and proton shell structures. In N=50 isotones, E1 modes exhibit varying IS and IV properties with smooth transitions as neutron excess increases. Our results suggest that compressional ISD strengths could provide valuable insights into the slope parameter of the nuclear equation of state. The observed dependence on nuclear shell structures and neutron–proton correlations highlights the need for precise measurements and further research in nuclear physics.